Happiness and Unemployment Status: The Case of Universiti Utara Malaysia - Muhd Yahya, Ab Rahman (2011)
Unemployment is a continuing problem in Malaysia or also other countries. Malaysia government has tried its best efforts to increase the graduate quality. For example, the government's expenditure in the higher education sector in Malaysia is seen to increase continuously from year to year. This shows the government is very concerned about education in enhancing human capital development and happiness of students. Thus, this survey is aimed to study the determinants of various measurements of happiness of UUM graduates, in particular, the impact of employment status of graduates. This study was conducted in UUM and data were obtained through self-administered questionnaire from 441 graduates who are attending the 23rd Convocation Ceremony, 2nd Assembly, Universiti Utara Malaysia (UUM). Results of this thesis indicate that the types of degrees, employment status and ethnic group are the significant determinant of happiness of UUM graduates. Based on the main findings, various policies like set up the new regulation, provide courses or programs for last semester students, provide the family sessions, provide the class or courses to all ethnic and theoretical implications are suggested.